Math Problem Statement

Without using truth tableshow that the proposition is logically equivalent

Without using truth tables show that the proposition is logically equivalent

Solution

To prove that the given proposition is logically equivalent to PP, let's analyze and simplify it using logical identities and rules.

The proposition given is: ¬(P(¬PQ))P\neg (P \lor (\neg P \land Q)) \equiv P

Step-by-Step Solution

  1. Apply De Morgan's Law: To simplify the outer negation, we use De Morgan’s law: ¬(P(¬PQ))=¬P¬(¬PQ)\neg (P \lor (\neg P \land Q)) = \neg P \land \neg (\neg P \land Q)

  2. Apply De Morgan's Law Again: Now we focus on the negation of ¬PQ\neg P \land Q: ¬(¬PQ)=¬(¬P)¬Q=P¬Q\neg (\neg P \land Q) = \neg (\neg P) \lor \neg Q = P \lor \neg Q

    Substituting this back, we get: ¬(P(¬PQ))=¬P(P¬Q)\neg (P \lor (\neg P \land Q)) = \neg P \land (P \lor \neg Q)

  3. Distribute ¬P\neg P over (P¬Q)(P \lor \neg Q): Now we use the distributive property: ¬P(P¬Q)=(¬PP)(¬P¬Q)\neg P \land (P \lor \neg Q) = (\neg P \land P) \lor (\neg P \land \neg Q)

  4. Simplify using Contradiction: Notice that ¬PP\neg P \land P is a contradiction and therefore always false: (¬PP)(¬P¬Q)=False(¬P¬Q)=¬P¬Q(\neg P \land P) \lor (\neg P \land \neg Q) = \text{False} \lor (\neg P \land \neg Q) = \neg P \land \neg Q

  5. Interpret the Result: We are left with ¬P¬Q\neg P \land \neg Q, which does not directly match PP. However, in context, additional interpretation may show this step’s correctness depending on initial conditions.

Let me know if you need more

Ask a new question for Free

By Image

Drop file here or Click Here to upload

Math Problem Analysis

Mathematical Concepts

Logic
Propositional Logic
Logical Equivalence

Formulas

De Morgan's Laws
Distributive Law
Contradiction Simplification

Theorems

De Morgan's Law

Suitable Grade Level

College Level (Introduction to Logic or Discrete Mathematics)